2018
DOI: 10.20546/ijcrar.2018.605.008
|View full text |Cite
|
Sign up to set email alerts
|

Review on Factors Affecting Success of Artificial Insemination

Abstract: Article InfoArtificial insemination (AI) is the manual placement of semen in the reproductive tract of the female by a method other than natural mating and it is among the group of technologies commonly known as assisted reproduction technologies (ART), whereby offspring are generated by facilitating the meeting of male and female gametes. It is intended to improve the fertility of low reproductive activity and low production capacity animals in animal reproduction. However, the success of artificial inseminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 9 publications
0
8
0
5
Order By: Relevance
“…However, other than handling and container management factors during distribution, several other factors that can affect the quality of semen must also be considered and regulated. These include genetics [ 14 , 15 ], breed, age [ 16 ], environment [ 14 , 15 ], and various management factors, including nutrition and semen collection management until completion of the freezing process to when the samples are ready for distribution [ 2 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, other than handling and container management factors during distribution, several other factors that can affect the quality of semen must also be considered and regulated. These include genetics [ 14 , 15 ], breed, age [ 16 ], environment [ 14 , 15 ], and various management factors, including nutrition and semen collection management until completion of the freezing process to when the samples are ready for distribution [ 2 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This technology can produce a high quantity of high-quality offspring within a short period by utilizing as many superior bulls as possible [ 1 ]. The measure of the success of AI on a farm is a high frequency of pregnant cows indicating an improved reproductive efficiency [ 2 ]. Conception rate (CR) is one indicator of fertility that can be used to assess reproductive efficiency [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bull fertility is related to semen quality [1,2]; the semen must contain good-quality sperm to fertilize oocytes until conception occurs [3]. Mishra et al [4] reported that the classical semen parameters were currently considered insufficient to predict a bull's fertility.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of frozen semen is one of the main factors that can influence the success of artificial insemination [1]. Good quality frozen semen has a positive effect on increasing fertility [2]. In its application, the quality of frozen semen is also influenced by various factors, one of which is the age of bulls.…”
Section: Introductionmentioning
confidence: 99%